Hospital morbidity due to mental and behavioral disorders in the Unified Health System in Sergipe-Brazil in 2018 - Cavalcante, K. M. H. (Scientific Electronic Archives, 2020)
In Brazil, despite the increasing use of information systems in research on morbidity in hospitalization authorizations, there are few epidemiological studies on hospitalizations for mental and behavioral disorders, although it is known that they imply a high financial cost for assistance in hospitalization. health and disability of the affected. The objective of this study was to describe the frequency of hospital morbidity due to mental and behavioral disorders in the Unified Health System (UHS) in Sergipe in 2018. This is a documentary research based on UHS hospital admissions records provided by the Department of Informatics of the UHS. In Sergipe, the largest number of hospitalizations in 2018 occurred in male patients, aged 30 to 39 years, and its higher frequency was due to schizophrenia, schizotypic and delusional disorders. There was a difference in the second cause of psychiatric hospitalizations in relation to sex. For men, the second most frequent diagnosis in hospitalizations for mental disorders was related to the use of other psychoactive substances, while for women were those of mood. These hospitalizations motivated by mental and behavioral disorders in 2018 occurred mainly in the capital Aracaju (95.5%). Knowing the profile of hospitalizations for mental disorders by the Hospital Information System can be useful not only for the epidemiological knowledge of these disorders and the planning of public health actions, but also for evaluating the effectiveness of public policies implemented in the mental health area. Â